2014
DOI: 10.1111/1440-1681.12258
|View full text |Cite
|
Sign up to set email alerts
|

The novel role and underlying mechanism of Wnt5a in regulating cellular cholesterol accumulation

Abstract: Cholesterol accumulation is a critical step during the development and progression of atherosclerosis. Recently, Wnt5a expression has been found to be markedly upregulated in both murine and human atherosclerotic lesions. However, the effect and mechanism of Wnt5a in atherosclerosis is poorly understood. In the present study, we investigated the effects and potential mechanisms of Wnt5a on cholesterol accumulation during atherosclerosis. We used RAW264.7 and vascular smooth muscle cells (VSMC) treated with oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…The results indicate that on average, the amount of Wnt5a protein present in the serum of atherosclerotic patients was significantly higher compared to that of healthy controls [36]. Recently, Wnt5a was shown to be involved in the regulation of cholesterol accumulation in mouse macrophages [37]. This finding is in line with results from our lab that show that Wnt5a modulates the expression of scavenger receptors in THP-1 cells, suggesting a role for Wnt5a during foam cell formation [38].…”
Section: Wnt5a In Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicate that on average, the amount of Wnt5a protein present in the serum of atherosclerotic patients was significantly higher compared to that of healthy controls [36]. Recently, Wnt5a was shown to be involved in the regulation of cholesterol accumulation in mouse macrophages [37]. This finding is in line with results from our lab that show that Wnt5a modulates the expression of scavenger receptors in THP-1 cells, suggesting a role for Wnt5a during foam cell formation [38].…”
Section: Wnt5a In Atherosclerosismentioning
confidence: 99%
“…In the early stages of atherosclerosis, inflammation of the endothelial wall can activate the endothelial cells to secret Wnt5a, and this Wnt5a could play an important role in the recruitment of monocytes to the site of injury [39]. Additionally, based on the recently reported role of Wnt5a in cholesterol accumulation, it is possible that Wnt5a may contribute in the formation of foam cells [37, 66]. During acute events or complications developed in vulnerable atherosclerotic plaques, Wnt5a may play a role as an inflammatory regulator by modulating the expression of biological mediators like IL-6, IL-1β, cyclooxygenase-2 etc.…”
Section: Wnt5a In Other Inflammatory Diseasesmentioning
confidence: 99%
“…Recent data suggests that upregulation of Abca1 by Wnt5a in RAW264.7 myeloid cells following oxLDL treatment reduces lipid accumulation via enhanced reverse cholesterol transport[131]. Similarly, Boucher, Herz, and colleagues have shown that Wnt5a upregulates Abcg1 and inhibits 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase and synthetase in mouse embryonic fibroblasts, thereby limiting the intracellular accumulation of cholesterol[132].…”
Section: Introductionmentioning
confidence: 99%
“…Among 42 pathways, in the previous sections we reported that 14 pathways were associated with HDL and LDL. From the literatures, we also know that unsaturated fatty acids stimulated the uptake of the LDL particles [ 53 ], PPAR signaling pathway was correlated with blood pressure [ 54 ], purine metabolism was associated with SBP [ 55 ], Wnt signaling pathway mediated cholesterol transportation [ 56 ], glycerolipid metabolism pathway was correlated with total cholesterol [ 57 ], focal adhesion pathway was involved in lipid modulation [ 58 ], Cell adhesion molecules was correlated with blood pressure [ 59 ].…”
Section: Resultsmentioning
confidence: 99%